Interspecific aggression in sympatry between congeneric tropical birds. (8th July 2021) - Drucker, Jacob R; Senner, Nathan R; Gomez, Juan Pablo
Abstract: Interspecific aggression may shape species distributions through competitive exclusion, resulting in spatial segregation, or facilitate sympatry as an adaptive mechanism for resource partitioning. Competitive exclusion results from asymmetric aggression of one species towards another, but if the aggressive relationship between species is symmetric, they may persist in sympatry. Interspecific aggression is widely cited as a mechanism for maintaining the distributional limits of tropical birds, but how it shapes the spatial dynamics of competing species that are sympatric over larger geographic areas is less clear. To address this issue, we conducted reciprocal playback experiments on two congeneric Antbirds — Thamnophilus atrinucha and T. doliatus — that occur in sympatry across a habitat matrix in Colombia to characterize their relationship as symmetrically or asymmetrically aggressive and analyzed point count data to assess the degree to which they occur sympatrically. We found weak evidence for competitive exclusion, with the larger T. doliatus responding asymmetrically to T. atrinucha, and the two species having a low co-detection rate during point counts. However, despite their 22% difference in body size, T. atrinucha still responded to T. doliatus playback in over half of our trials, and the two species co-occurred on nearly 25% of point counts, indicating that interspecific aggression does not drive complete spatial segregation. Our findings highlight how the degree to which one species can competitively exclude another may vary, especially across a dynamic landscape. Abstract : Coexistence between competitors is a compromise where larger species usually have the final word. We simulated competitive encounters in the field and analyzed survey data to see if body size predicted the direction of aggression and spatial segregation of two sympatric bird species. Aggression favored the larger species, but the smaller responded aggressively more than expected by body size, suggesting that additional factors, like habitat, influence competitive interactions between species.